Integration of FMEA, LTA, and Fishbone Diagrams in the application of RCM II on KN–02 Gas Compressors - Muhamad Ari; Anda Iviana Juniani; Tri Andi Setiawan; Bayu Wiro Karuniawan; Habib Ngumar Faruq; Anum Kusuma Lendie; Firhan Rafif Rizqullah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Gas compressors are vital equipment in the oil and gas industry that function to maintain the smooth production and transportation of natural gas. Compressor failure can cause significant downtime, financial losses, and safety risks. This study aims to evaluate the maintenance policy of the KN-02 gas compressor at the Nibung Gas Compressor Station (SKG) using the Reliability Centered Maintenance II (RCM II) method. Engine fault data was collected in the period September–October 2024 and analyzed through Failure Mode and Effect Analysis (FMEA), Logic Tree Analysis (LTA), and Fishbone Diagram to identify critical failure modes and root causes. Furthermore, the proposed treatment strategy was formulated using the RCM II Decision Worksheet. The results of the analysis showed three critical components with the highest Risk Priority Number (RPN) values, namely cylinder oil supply failure (RPN = 671), valve suction/discharge (RPN = 662), and packing rod (RPN = 577). Based on the results of the LTA, the recommended types of maintenance include scheduled restoration, scheduled discard, and condition-directed maintenance. Fishbone's analysis indicates that the root cause comes from material wear factors, lubrication quality, and maintenance procedure errors. With the implementation of an RCM II-based maintenance strategy, compressor engine downtime is expected to be reduced by more than 40%, while improving the operational reliability of the system. This study confirms that RCM II is effective as a systematic approach in determining optimal oil and gas machinery maintenance policies.